Estudo de um modelo teórico de uma máquina-ferramenta - Lamy, Carlos Alfredo (1979)
A theoretical model of a machine tool is studied which takes into consideration the vibration of the workpiece and the tool in relation to the part of the structure that can be assurred to be rigid. The greatestadvantage of this study is the simplicity of its practical application. Employing the sarne parameters necessary for the calculation of classical models, one can obtain with a reduced number of mathematical operations the frequency bands in which the machine has good performance.